(3QaY GdMLH GdeSJhQI Yf eMGSf GdebUhQIs - (3CHh GdbGSe eMeO Hf CMeO Hf eMeO GdMSjfj GdSHJi GdeYQha HGdTQja CHh GdZQfGWis; (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG JCedJ ebUhQI GdGeGe GdChMO CHj GdMSf CdajJgG JLeY VQhHG ef GdGMSGS hJTJed Ydi CaGfjf ef GdHjGf s
(3BNQgG (B:s
(3hGJjJ HeG jMUd efg GdbGQF Ydi QTGO abO hajJ HeG hYOJ s
(3GdfSNI HgG MhGTs
(3HgG HjGV ai GdhQbI (B45 (3H hYdjgG JUMjMGJs
(3fSNI QGHYI JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3hYdjg JMHjS CHj GdYHGS GdefUhQ HGddg Ydi LGeY GdbQhjjf HJGQjN (B1353 (3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs